RESPON SISWA TERHADAP LEMBAR KERJA PESERTA DIDIK (LKPD) MATERI BIOTEKNOLOGI PRODUK FERMENTASI LOKAL DI SMA NEGERI - Nurhaty Purnama Sari; Fenny Agustina; Riska Henilian Saputri (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
This study aims to determine students' responses to local fermented biotechnology Worksheets. This research was a type of qualitative descriptive research. Data collection used a questionnaire with Likert scale. Data trials were carried out with 2 scales, they are small scale of 8 respondents and large scale of 28 respondents. Based on the assessment of the results of the questionnaire that given to small-scale respondents, reached 89% in the very good category, while the large-scale respondents amounted to 87.81% in the very good category.